Freeze-thaw stability of enzyme-treated filled bicho bicho - Caro, Ma. Chrisitne Cecilia Cuspao
ABSTRACT The study aimed to evaluate the stability of an enzyme-treated bicho bicho subjected to 5 consecutive cycles of freezing (-18 ºC, 48 h) and thawing (12 ºC, 24 h). An acceptable base choco-peanut filled bicho bicho was developed from the published recipe of Fabian (1972) through a multi-level sensory evaluation (n = 30). The base-filled bicho bicho was then treated with maltogenic α-amylase at 0.001% and 0.01%, and pentosanase at 0.002% and 0.012% (wt/wt flour basis). The enzyme-treated bicho bicho was compared with a control through sensory and physico-chemical tests. The 0.012% pentosanase-treated bicho bicho obtained the highest mean acceptability scores in overall acceptability and most of the specific attributes at 5% level of significance. The physico-chemical, microbiological, and consumer acceptability of the 0.012% pentosanase-treated bicho bicho was monitored over 5 freeze-thaw cycles. The sensory results showed that despite physico-chemical changes, the 0.012% pentosanase-treated choco-peanut filled bicho bicho remained stable in terms of overall consumer acceptability with 5 freeze-thaw cycles. Microbiological results also showed that the enzyme-treated bicho bicho remained within satisfactory levels for TPC, TCC, and YMC. The results indicated that filled bicho bicho could be subjected up to 5 freeze-thaw cycles and remain acceptable for consumption. The study showed that the addition of pentosanase was beneficial for ready-to-eat bicho bicho but not necessarily advantageous for bicho bicho subjected to freeze-thaw cycles. The use of pentosanase was recommended for commercial production of ready-to-eat bicho bicho. Further studies on the effect of amylase, the other enzyme studied in Phase 2, on the freeze-thaw stability of choco-peanut filled bicho bicho was also recommended.